Influence of cultivation spacing and two pruning times on stem carbohydrate in coffee - Pereira, Sérgio Parreiras; Baliza, Danielle Pereira; Santos, Meline Oliveira; Alves, José Donizeti; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2014)
The objective of this work was to evaluate coffee plant stem carbohydrate contents in function of the cultivation spacing and at two pruning times. The experiment was conducted on a crop in the Fazenda Experimental da Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG), in Machado, MG, implanted in January of 1992. The experimental design was in random blocks in a 4 x 3 x 2 factorial outline, being four spacings bewteen rows (2.0; 2.5; 3.0 and 3.5 m), three spacings among the plants in the planting row (0,5; 0,75; 1,0 m), and two pruning times (one early, soon after harvest in July 2002 and the other late, in the month of January, 2003), totaling 24 treatments with three repetitions. In July, 2002 and in January, 2003 the stump type prunings were conducted, when the coffee plant stem disk samples were collected and the accumulated of stem carbohydrate content were analyzed. The treatments were also appraised as to the productivity and the production per plant in the year of 2002. The productivity is negatively influenced by the increase of the spacing among the planting rows, while the per plant production is higher at the spacing of 1.00 m among plants. In greater planting row is maintained in the levels of total soluble sugars of a pruning time for another. The starch content increased in all the spaces between the pruning times. When the pruning is conducted six months after the harvest of the fruits, the coffee plants present higher stem carbohydrates levels.